Takhrij and Syarah Hadith of Agrotechnology Study of the Benefits of Pomegranate from a Science Perspective - Enjang Muhamad Hayatudin; Wahyudin Darmalaksana; Amalia Purdianty (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith regarding the properties of pomegranate. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study are the health benefits of pomegranate. The conclusion of this research is that pomegranate based on takhrij and syarah hadith is suitable to be used as a cure for diseases and for beauty.